Booklice and Silverfish - P.G. Koehler; D. Branscome; F.M. Oi (EDIS)
This document provides an overview of booklice and silverfish, detailing their biology, life cycles, and control methods. Booklice, or psocids, feed on fungi and organic matter, thriving in warm, humid environments. Silverfish and firebrats, belonging to the Order Zygentoma, damage materials high in protein, sugar, or starch. Effective control includes reducing humidity, proper storage, and using insecticides. The document emphasizes the importance of hygiene and preventive measures to manage infestations.